Efikasi Gen RB pada Tanaman Kentang Transgenik Katahdin SP904 dan SP951 terhadap Empat Isolat Phytophthora infestans dari Jawa Barat - Ambarwati, Alberta Dinar; Sumaraw, S M; Purwito, Agus; Herman, Muhammad; Suryaningsih, E.; Aswidinnoor, Hajrial (Jurnal AgroBiogen, 2011)
Efficacy of RB gene in transgenic potato Katahdin SP904and SP951 to West Java isolates of Phytophthorainfestans. A. Dinar Ambarwati, S.M. Sumaraw, AgusPurwito, M. Herman, E. Suryaningsih, and HajrialAswidinnoor. Potato late blight, caused by Phytophthorainfestans is one of the most devastating plant disease. Potatoyield losses due to this disease ranged from 47-100%. Amajor late blight resistance gene, called RB, previously wasidentified in the wild potato species Solanumbulbocastanum. RB gene has been integrated into cultivatedpotato Katahdin using Agrobacterium-mediated transformation,and showed durable and broad spectrum resistanceeither in laboratory assay or in confined field trial. Evaluationof transgenic Katahdin SP904 and SP951 was conducted toverify whether the RB gene with broad spectrum to allknown races of P. infestans in the United States and inToluca, Mexico was also effective against P. infestansisolates in Indonesia. Efficacy of RB gene was evaluated forfoliar and tuber resistance to West Java isolates. TransgenicKatahdin were more resistant in foliar than non transgenicplants, at 14 days after inoculation. Diseases intensity oftransgenic Katahdin SP904 and SP951 were 19.8-43.8%,whereas non transgenic Katahdin, Granola, and Atlanticwere 46.9-100%. In contrast to the foliar resistancephenotype, RB-containing tubers in transgenic Katahdin didnot exhibit increased resistance to Lembang, Pangalenganand Galunggung isolates. Tubers of transgenic KatahdinSP904, SP951, and non transgenic Katahdin showed lesionvolume of 0.93, 0.91, and 0.91 cm3, respectively. RB gene intransgenic Katahdin showed efficacy against late blight P.infestans in foliar, but did not showed efficacy in tuber.Transgenic Katahdin RB thus providing a potential source ofresistance for breeding programs.